2018
DOI: 10.1177/0956797617719082
|View full text |Cite
|
Sign up to set email alerts
|

Event-Based Conformity Versus Regression to the Mean: A Comment on Kim and Hommel (2015)

Abstract: Kim and Hommel (2015) provided an intriguing alternative explanation for conformity effects. Building on the theory of event coding (TEC;Hommel, 2009;Hommel, Müsseler, Aschersleben, & Prinz, 2001), they assumed that one's own and others' actions are represented in comparable ways, so that people may fail to distinguish between those two action categories. As a consequence, "people's actions that have no social meaning should induce conformity effects" (p. 484).Building on a paradigm previously used to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…We hasten to add that this observation must not be taken as unequivocal evidence for the validity of our theoretical background. As argued by Ihmels and Ache (2018) and partly confirmed by Kim and Hommel (2018), the paradigm used by Kim and Hommel (2015) and previous researchers is sensitive to regression-to-the-mean effects, which implies that the effect that Kim and Hommel (2015) were able to extend to non-social conditions was actually not a real conformity effect. What we do want to emphasize, however, is that we consider our approach the first truly mechanistic account of conformity behavior which allows for much more specific predictions than the previously suggested descriptive accounts.…”
Section: Non-mechanistic Theorizingmentioning
confidence: 79%
“…We hasten to add that this observation must not be taken as unequivocal evidence for the validity of our theoretical background. As argued by Ihmels and Ache (2018) and partly confirmed by Kim and Hommel (2018), the paradigm used by Kim and Hommel (2015) and previous researchers is sensitive to regression-to-the-mean effects, which implies that the effect that Kim and Hommel (2015) were able to extend to non-social conditions was actually not a real conformity effect. What we do want to emphasize, however, is that we consider our approach the first truly mechanistic account of conformity behavior which allows for much more specific predictions than the previously suggested descriptive accounts.…”
Section: Non-mechanistic Theorizingmentioning
confidence: 79%
“…This conjecture draws from a recent study employing a similar paradigm, in which participants' reappraisal was also influenced by feedbacks with no social meaning (Kim and Hommel, 2015, but see Klucharev et al, 2009). Third, scholars suggested a potential confound of the initial rating, which depends on the position of the feedback (Ihmels and Ache, 2018;Kim and Hommel, 2018). Indeed, trials with large deviance in one direction are by definition those in which the initial rating is sufficiently distant from the physical boundary of the scale to allow the presentation of the feedback (see methods).…”
Section: General and Specific Effects In Feedback Processingmentioning
confidence: 99%
“…It has been argued that results from studies on conformity may be undermined by the phenomenon known as regression to the mean (RTM) 34,45 , that occurs when an extreme measurement at time 1 is more likely to be followed by a less extreme value at time 2. This makes a natural variation in repeated measures to look like an experimentally-induced change 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that the reliability of the ratings within the female group was fair, whereas the reliability of the ratings within the male group was poor, a result that further justifies our prior selection of the stimuli. It is also important to emphasize that this selection procedure was aimed at alleviating floor effects on the ratings that could have biased the results because of the RTM phenomenon 34,35,45,46 .…”
Section: Discussionmentioning
confidence: 99%